5 Elemen Pembentuk Citra Kota Di Kawasan Kota Lama Kupang - Poetri Yaumil Achir; Julia S. P. L. Baok; I Nyoman Rama Putra; Feryrius Fahik; Nyoman Warnata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
The elements that reveal the image of the city are the parts that make up the characteristics of the region. Elements that reveal the image of the city can be seen from kevin lynch theory (1960), divided into 5 elements, namely: Path (jaur), Edges (edges), District (Area), Nodes (nodes), Landmarks (tengeran). The purpose of this study is to find and find elements that reveal the image of the old city of kupang and want to try to solve problems found in the field such as 5 elements of urban imagery that are less visible in the old city area of Kupang, This study uses a rationalistic approach with qualitatively processed data. Data in the form of literature and maps are collected to see signs and findings in the field. Then devise a theoretical concept based on existing theories of research variables. In this research also carried out the process of method analysis of deduction, namely the effort to explain or predict the existence of facts / events at the research site according to the theoretical foundation that has been obtained. The findings of the study showed that at some point in the old city already revealed elements forming the image of the old city of Kupang which was influenced by the elements forming the city area in line with the socio-cultural and economic development of the people in the region.